AI on the front lines : AI progress can stall when end users resist adoption : developers must think beyond a project's business benefits and ensure that end users' workflow concerns are addressed - Kellogg, Katherine C.; Sendak, Mark; Balu, Suresh (MIT Sloan Management Review, 2022)
AI progress can stall when end users resist adoption, so developers must extend project goals to also address end user concerns. In a study of AI-based decision support tools, the authors observed frequent misalignment between project sponsors’ needs and end users’ priorities and preferences. They found that when developers ensure that end users’ concerns about workflow and autonomy are addressed, conflicting stakeholder interests can be reconciled and AI tools more readily adopted.